Efficacy and safety of a single dose of casirivimab and imdevimab for the prevention of COVID-19 over an 8-month period: a randomised, double-blind, placebo-controlled trial. Issue 10 (October 2022) - Herman, Gary A; O'Brien, Meagan P; Forleo-Neto, Eduardo; Sarkar, Neena; Isa, Flonza; Hou, Peijie; Chan, Kuo-Chen; Bar, Katharine J; Barnabas, Ruanne V; Barouch, Dan H; Cohen, Myron S; Hurt, Christopher B; et al.
Summary: Background: There is an unmet need for COVID-19 prevention in patient populations who have not mounted or are not expected to mount an adequate immune response to complete COVID-19 vaccination. We previously reported that a single subcutaneous 1200 mg dose of the monoclonal antibody combination casirivimab and imdevimab (CAS + IMD) prevented symptomatic SARS-CoV-2 infections by 81·4% in generally healthy household contacts of SARS-CoV-2-infected individuals over a 1-month efficacy assessment period. Here we present additional results, including the 7-month follow-up period (months 2–8), providing additional insights about the potential for efficacy in pre-exposure prophylaxis settings. Methods: This was a randomised, double-blind, placebo-controlled trial done in the USA, Romania, and Moldova in 2020–2021, before the emergence of omicron (B.1.1.529) and omicron-lineage variants. Uninfected and unvaccinated household contacts of infected individuals, judged by the investigator to be in good health, were randomly assigned (1:1) to receive 1200 mg CAS + IMD or placebo by subcutaneous injection according to a central randomisation scheme provided by an interactive web response system; randomisation was stratified per site by the test results of a local diagnostic assay for SARS-CoV-2 and age group at baseline. COVID-19 vaccines were prohibited before randomisation, but participants were allowed to receive COVID-19 vaccination during the follow-up period. Participants who developed COVID-19 symptoms during the follow-up period underwent RT-PCR testing. Prespecified endpoints included the proportion of previously uninfected and baseline-seronegative participants (seronegative-modified full analysis set) who had RT-PCR-confirmed COVID-19 in the follow-up period (post-hoc for the timepoints of months 2–5 and 6–8 only) and underwent seroconversion (ie, became seropositive, considered a proxy for any SARS-CoV-2 infections [symptomatic and asymptomatic]; prespecified up to day 57, post-hoc for all timepoints thereafter). We also assessed the incidence of treatment-emergent adverse events. This study is registered with ClinicalTrials.gov, NCT04452318 . Findings: From July 13, 2020, to Oct 4, 2021, 2317 participants who were RT-PCR-negative for SARS-CoV-2 were randomly assigned, of whom 1683 (841 assigned to CAS + IMD and 842 assigned to placebo) were seronegative at baseline. During the entirety of the 8-month study, CAS + IMD reduced the risk of COVID-19 by 81·2% (nominal p<0·0001) versus placebo (prespecified analysis). During the 7-month follow-up period, protection was greatest during months 2–5, with a 100% relative risk reduction in COVID-19 (nominal p<0·0001; post-hoc analysis). Efficacy waned during months 6–8 (post-hoc analysis). Seroconversion occurred in 38 (4·5%) of 841 participants in the CAS + IMD group and in 181 (21·5%) of 842 in the placebo group during the 8-month study (79·0% relative risk reduction vs placebo; nominal p<0·0001). Six participants in the placebo group were hospitalised due to COVID-19 versus none who received CAS + IMD. Serious treatment-emergent adverse events (including COVID-19) were reported in 24 (1·7%) of 1439 participants receiving CAS + IMD and in 23 (1·6%) of 1428 receiving placebo. Five deaths were reported, none of which were due to COVID-19 or related to the study drugs. Interpretation: CAS + IMD is not authorised in any US region as of Jan 24, 2022, because data show that CAS + IMD is not active against omicron-lineage variants. In this study, done before the emergence of omicron-lineage variants, a single subcutaneous 1200 mg dose of CAS + IMD protected against COVID-19 for up to 5 months of community exposure to susceptible strains of SARS-CoV-2 in the pre-exposure prophylaxis setting, in addition to the post-exposure prophylaxis setting that was previously shown. Funding: Regeneron Pharmaceuticals, F Hoffmann-La Roche, US National Institute of Allergy and Infectious Diseases, US National Institutes of Health.